Quantification of Harm in Damages Actions for Antitrust Infringements: Insights from German Cartel Cases - Hans W. Friederiszick; Lars-Hendrik Röller (European School of Management and Technology (ESMT), 2010)
This paper argues that empirical economic analysis in court proceedings is subject to important economic and legal restrictions, cumulating in a fundamental trade-off between accuracy and practicality. We draw lessons from two influential German court cases the paper wholesaler cartel decision of 2007 and the cement cartel decision of 2009. We characterise the trade-offs arguing that they need to be well understood, made transparent, and that decisions on how to proceed in light of these trade-offs have to be taken upfront by the court. In this respect, we believe that the three-step procedure (design, application, and robustness checks) followed by the German court in the cement case is well suited to meet the appropriate legal standard and requirements, both with respect to accuracy and practicality.
urn:nbn:de:101:1-201106143656
Keywords: L12; L41; K21; K41; C10; 650; antitrust law; horizontal anticompetitive practices; quantification of damages; Kartell; Kartellrecht; Rechtsprechung; Wettbewerbsrecht; Deutschland